Early Cermet Microcircuits - Hesketh, Dean D. (1964)
This photograph is part of a series of marketing images used to demonstrate the small size of Helipot products. "Cermet" refers to ceramic metals.
Keywords: Microelectronics; Ceramic metals; Beckman Instruments, Inc.